The Association between Depressive Symptoms and Physical Diseases in Switzerland: A Cross-Sectional General Population Study - Rodic, Donja; Meyer, Andrea Hans; Meinlschmidt, Gunther (Frontiers in Public Health, 2015)
Objective: To estimate the association between depressive symptoms and physical diseases in Switzerland, as respective findings might inform about future estimates of mental and physical health care costs. Methods: A population-based study, using data from the Swiss Health Survey collected by computer assisted telephone interviews and additional written questionnaires during the year 2007 (n = 18,760) in Switzerland. The multistage stratified random sample included subjects aged 15 and older, living in a private Swiss household with a telephone connection. Complete data was available for 14,348 subjects (51% of all subjects reached by telephone). Logistic regression analyses were used to estimate the associations between depressive symptoms and any physical disease, or a specific physical disease out of 13 non-communicable physical diseases assessed with a self-report checklist on common physical diseases. Analyses were adjusted for sex, age, education, occupation and household income. Results: In the adjusted models depressive symptoms were associated with arthrosis and arthritis (Odds Ratio [OR] = 1.79, 95% Confidence Interval [CI] = 1.28−2.50) and any physical disease (OR = 1.67, 95% CI = 1.33−2.10) after controlling for multiple testing. Conclusion: Our findings contribute to a better understanding of the comorbidity of depressive symptoms and arthrosis and arthritis in Switzerland and might have implications for more precise future estimates of mental and physical health care costs.